Diphenyl guanidine vulcanization accelerators enable sulfurized polyacrylonitrile cathode for high capacity and ether-compatible by fast kinetic. (15th October 2021) - Wang, Yu; Zhang, Yunpeng; Shuai, Yi; Chen, Kanghua
Abstract: Sulfurized polyacrylonitrile (SPAN) cathode shows excellent electrochemical performance in carbonate electrolyte for lithium-sulfur batteries. However, the limited redox conversion rate of SPAN cathode in ether electrolyte would lead to high solubility of the intermediate polysulfide Li2 Sn (n ≤ 4) and shuttling, resulting in a low performance of corresponding lithium-sulfur battery, even though ether-based electrolytes are more suitable in terms of Li metal anode. In addition, SPAN is comparatively lower sulfur loading (<50 wt%) reduced its value. Improving the sulfur loading and accelerate the redox conversion of SPAN to be compatible with ether electrolyte will be one of the most promising cathode of lithium-sulfur batteries. Here, we introduced a sulfurized polyacrylonitrile cathode (SPAN-DG) with high sulfur loading (52 wt%) and high conductivity prepared by diphenylguanidine as vulcanization accelerator into lithium-sulfur battery based on ether electrolyte. This study found that SPAN-DG cathode with high conductivity can fast reaction kinetics and successfully inhibit the dissolution of lithium polysulfide and shuttle in ether electrolytes, shows good electrochemical performance. SPAN-DG cathode deliver a specific capacity of 879 mAh g −1 and 661 mAh g −1 (based on the mass of cathode) at rates of 0.1C and 1C (1C = 700 mA g −1 ), respectively. Highlights: SPAN-DG cathode shows high sulfur loading and high conductivity. SPAN-DG cathode can inhibit dissolution of lithium polysulfide in ether electrolyte. SPAN-DG deliver 895 mAh g −1 discharge capacity in ether electrolyte for Li–S battery.